PENGEMBANGAN MODEL PELATIHAN KEPALA SEKOLAH BERBASIS SEULANGKE UNTUK PENINGKATAN KOMPETENSI RISK-TAKING DAN LEGITIMASI KULTURAL DI ACEH BESAR - Maidar, Maidar; M. Daud, Yusri; Al-Ghifary, Farhan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The leadership competence gap in Indonesia, particularly Aceh (UKKS score 53.89), stems from the dysfunction of conventional training. Previous training fails to incorporate futuristic competencies (risk-taking, negotiation) and neglects cultural legitimacy, resulting in a significant execution gap. This study aims to develop and validate the Seulangke-Based School Principal Training Model to bridge this gap through the lens of Sociocultural Theory. Utilizing the R&D ADDIE Model methodology and a Quasi-Experimental design (N=27), the research operationalizes the local Acehnese wisdom, Seulangke (wise, dignified, negotiator), as a cultural tool to mediate competence internalization. The developed model proved Highly Valid (mean score 4.64–4.71) and Highly Practical (85.9%). The effectiveness test demonstrated a significant improvement in competence for the Experimental Group, yielding an N-Gain Score of 0.649 (Medium-to-High category). This increase, particularly in Futuristic Competencies, was strongly confirmed by the T-Test (p < 0.05). The findings empirically validate that the Seulangke Model successfully fosters moral authority, which is crucial for internalizing managerial practices and overcoming the educational leadership execution gap.